Iconic visions: shaping Yinchuan’s future tourism business through landmark perceptions - Ji, Guangyao; Abd Manan, Mohd Shahrudin (Asian Scholars Network, 2024)
With the advancement of today’s technological image culture, the role of visual landmarks in shaping a city’s appeal and enhancing its tourism business has become increasingly crucial. Visual landmarks serve not only as symbols of a city’s identity but also as magnets that attract tourists and local residents alike, shaping their perceptions and experiences of the city. Against this backdrop, this article explores future design concepts for visual landmarks in Yinchuan city, Ningxia Hui Autonomous Region, China, with a focus on place branding. The exploration takes into account insights derived from a survey of 400 respondents, a diverse sample comprising both local residents and tourists. The survey investigation follows four methodological procedures: translation, coding, categorization, and thematization, aimed at understanding thematic patterns in the collected data. The thematic analysis reveals five key themes central to the consideration of the visual landmarks: historical and cultural elements, geocultural features, aesthetic considerations, urban infrastructure, and local specialties. These themes reflect not only the preferences and perceptions of the respondents but also their emotional connections and memorable experiences. As exploratory futurological research, this article emphasizes the significance of public perceptions and thematic design elements that can enhance a city’s image and tourism brand. It paves the way for an expanded research agenda by integrating future imagination and fostering collaborative efforts to leverage tourism as a catalyst for broader socioeconomic development.